Microbiome in human health and disease. (1st June 2013) - Madupu, Ramana; Szpakowski, Sebastian; Nelson, Karen
Metagenomic studies have truly revolutionised biology and medicine, and changed the way we study genomics. As genome sequencing becomes cheaper, it is being applied to study complex metagenomes. 'Metagenome' is the genetic material recovered directly from an environmental sample or niche. By delivering fast, cheap, and large volumes of data next Generation Sequencing (NGS) platforms have facilitated a deeper understanding of the fundamentals of genomes, gene functions and regulation. Metagenomics, also referred to as environmental or community genomics, has brought about radical changes in our ability to analyse complex microbial communities by direct sampling of their natural habitat paving the way for the creation of innovative new areas for biomedical research. Many metagenomic studies involving the 'human microbiome' have been undertaken to date. Samples from of a number of diverse habitats including different human body sites have been subject to metagenomic examinations. Huge national and international projects with the purpose of elucidating the biogeography of microbial communities living within and on the human body, are well underway. The analysis of human microbiome data has brought about a paradigm shift in our understanding of the role of resident microflora in human health and disease and brings non-traditional areas such as gut ecology to the forefront of personalised medicine. In this chapter, we present an overview of the state-of-the-art in current literature and projects pertaining to human microbiome studies.